1994
DOI: 10.1515/cclm.1994.32.4.285
|View full text |Cite
|
Sign up to set email alerts
|

Development of Enzyme Immunoassays Specific for Keratan Sulphate- and Core-Protein-Epitopes of the Large Aggregating Proteoglycan from Human Articular Cartilage

Abstract: Fischer et aL: Novel cnzyme immuno assays for kcratan sulphate and aggrecan corc-protein 285 Eur. J. Clin. Chem. Clin. Biochem. Vol. 32, 1994, pp. 285-291 © 1994 Summary:In the course of chronic inflammatory and degenerative joint diseases proteoglycans are degraded by the action of proteases and oxygen radicals. Therefore, proteoglycan fragments, released from cartilage into the peripheral blood, might be useful markers of cartilage degradation. Sensitive enzyme immunoassays are useful for the detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 12 publications
0
15
0
1
Order By: Relevance
“…Determination of keratan sulfate concentration in serum was performed using the monoclonal antibody 5-D-4 (Medac) in an antigen-inhibition assay as described previously (Fischer et al, 1994(Fischer et al, , 1996Ku È chle et al, 1999;Cursiefen et al, 2000b).…”
Section: Methodsmentioning
confidence: 99%
“…Determination of keratan sulfate concentration in serum was performed using the monoclonal antibody 5-D-4 (Medac) in an antigen-inhibition assay as described previously (Fischer et al, 1994(Fischer et al, , 1996Ku È chle et al, 1999;Cursiefen et al, 2000b).…”
Section: Methodsmentioning
confidence: 99%
“…The study of glycoprotein antigens after deglycosylation has also indicated the importance of some carbohydrate determinants in autoimmune diseases [11,[103][104][105][106], and has revealed that carbohydrate determinants can be important in antigens used for diagnostic tests for circulating antibodies in autoimmune [107] and infectious diseases [22]. T-cell recognition of collagen in rheumatoid arthritis is dependent on carbohydrate epitopes, and removal of the hydroxylysine-linked sugars with TFMS indicated that the carbohydrate was necessary for reactivity of the T-cell clones [11,106].…”
Section: Determination Of the Reactivity Of Antibodies With Protein Omentioning
confidence: 99%
“…Removal of keratan sulphate chains with TFMS increased reactivity of T-cells with aggrecan in mice [103] and in rheumatoid arthritis patients [104,105]. An antibody against the core protein of aggrecan was shown to be a useful marker for inflammatory disease, as synovial fluid from patients with degenerative joint diseases had increased proteoglycan fragments that could be detected with this antibody [107]. Tests of serum for antibodies against T. gondii used for diagnosis of toxoplasmosis can be performed using surface antigen I expressed by P. pastoris.…”
Section: Determination Of the Reactivity Of Antibodies With Protein Omentioning
confidence: 99%
“…Degradation products of aggrecan can be detected in body fluids, including synovial fluid, where they reflect aggrecan turnover [38,39]. Previous studies show that the proteoglycan aggrecan is a target for autoreactive T cells in RA and ankylosing spondylitis [40-42].…”
Section: Discussionmentioning
confidence: 99%